Scientific Analysis: Mepe Kasur Tradition as a Repellent and Permanence in Banyuwangi, Indonesia - Nisa, Wilda Muhimmatun; Projosantoso, A K (KOMUNITAS: International Journal of Indonesian Society and Culture, 2020)
Numerous traditional activities in Banyuwangi are still running in these time. One of traditions that still currently runs is Mepe Kasur tradition. Mepe is sunning, and Kasur is bed. Kemiren’s people, Banyuwangi assume that the source of the disease comes from the seat. mattress is removed and dried under the sun, so all of diseases will vanish. This research was descriptive qualitative method. Data collection technique were collected by literature’s review. Based on the results of research, each person surrenders about 1.5 million dead skin cells per hour and emits 0.9 liters every day, including during sleep. Besides, practically each person spends sleeping time on the mattress around 8 hours or more. At this time, body always contacts above the bed with its equipment so that it can be imagined through sleeping at tens of millions of dead skin cells, fall out, which can be attached in the whole of bedding. Black and red are the colors, the highest emissivity, thus they can absorb heat quickly, this is why black and red can present philosophical protection from all kinds of diseases and disasters, and permanence.